Identification of metal content in food using gravimetric and iodometric methods: The case on children's food - Nelius Harefa; Saronom Silaban (Pascasarjana Universitas Negeri Medan, 2020)
The metal content is one indicator of the eligibility of food consumption, including food for children. In this research, identification of Lead (Pb), Mercury (Hg), Cadmium (Cd), and Arsenic (As) metals on pentol, bakso, cilok, cireng, and cimin samples by gravimetric and iodometric methods. The identification of metals by the gravimetric method shows that the metal content in all samples is below the threshold, where the highest metal content is the lead metal in the cimin sample of 0.0439 mg/kg. The identification of metals by the iodimetry method showed that the metal content in all samples was below the threshold, where the highest metal content is the lead metal in the cimin sample of 0.0436 mg/kg. Thus, all samples are categorized as safe for consumption. Keywords: Gravimetric, Iodometric, Metals content